2018
DOI: 10.1097/pas.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Carcinomas With Mucinous and Neuroendocrine Differentiation

Abstract: Amphicrine carcinoma is a distinct type of carcinoma characterized by synchronous exocrine and endocrine differentiation within the same tumor cell. Such tumors are exceedingly rare and most commonly recognized in the gastrointestinal tract. In the lung, sporadic descriptions of such lesions exist. This report presents 3 more such tumors, expanding the spectrum of amphicrine carcinomas in this organ. The patients were 3 men, 53 to 78 years of age (mean: 63 y) and all were current or former smokers. In one pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Napsin A was previously considered not to be expressed in LCNEC, but recent reporting of napsin A positivity in LCNEC, 25,57 and cases that are borderline AC-LCNEC, 58 or borderline basaloid SqCC-LCNEC, 59 questions its diagnostic use. In our borderline cases (solid AC with more than 1 positive NE marker) we included data from previous mutation analyses, as it may be argued that RB1 mutations (or loss) favor a true NE lineage (''SCLC-like''), while cases with KRAS/STK11/KEAP1 or PI3K/AKT/mTOR mutations more resemble NSCLC on a molecular level (''NSCLClike'').…”
Section: Discussionmentioning
confidence: 99%
“…Napsin A was previously considered not to be expressed in LCNEC, but recent reporting of napsin A positivity in LCNEC, 25,57 and cases that are borderline AC-LCNEC, 58 or borderline basaloid SqCC-LCNEC, 59 questions its diagnostic use. In our borderline cases (solid AC with more than 1 positive NE marker) we included data from previous mutation analyses, as it may be argued that RB1 mutations (or loss) favor a true NE lineage (''SCLC-like''), while cases with KRAS/STK11/KEAP1 or PI3K/AKT/mTOR mutations more resemble NSCLC on a molecular level (''NSCLClike'').…”
Section: Discussionmentioning
confidence: 99%
“…Carcinomas with co-existing NE and mucinous differentiation in the same cell rather than in distinct geographic areas (so-called amphicrine carcinomas) do rarely occur in the lung 112 , although they are better described in the digestive tract 113 . The WHO taxonomy for these is currently lacking, but conceptually such tumor may be regarded as a type of combined carcinomas.…”
Section: Combined Neuroendocrine Carcinomasmentioning
confidence: 99%
“…As early as 1988, Müller K et al rst proposed the so-called amphicrine cells which contain mucous vacuoles as well as granules of neurosecretory type, found in goblet cell hyperplasia and in basal cells [10]. Weissferdt A et al reported 3 cases of pulmonary carcinomas with mucinous and neuroendocrine differentiation, expanding the spectrum of amphicrine carcinomas [11],…”
Section: Discussionmentioning
confidence: 99%